Field Observations On The Nature And Extent of Damage by Indian Desert Termites and Their Control - Parihar, D R (Annals of Arid Zone, 2016)
Studies on the nature and extent of damage showed that desert termites attacked not only the roots of the seedlings but also the trunk and bark of the trees. Monomorium longi Forel. Pheidole smythiesi Forel, Humbertiella indica Sauss, Calotes versicolor and Funambulus pennanti were recorded as new predators of the termites in India. 0.02 percent of endrin E.C., and 0.03% of aldrin E.C., were found most effective against Odontotermes brunneus, attacking the Dalbergia sissoo trees for one year; while 5% aldrin and 10% BHC dust @ 10 kg a.i./ha proved to be effective against Microcerotermes tenuignathus infesting wheat crop.